Catalytic Performance of La-Ni/Al2O3 Catalyst for CO2 Reforming of Ethanol - Vo, Dai-Viet N.; Mahadi, Bahari; Phuc, Nguyen Huu Huy; Alenazey, Feraih; Vu, Khanh B.; Nurul Aini, Razali (Elsevier B.V., 2017)
La-promoted 10%Ni/Al2O3catalyst was prepared by wet impregnation method and evaluated for ethanoldry reforming at various reaction temperatures and partial pressure of reactants. Ni particles were finelydispersed on catalyst surface and catalyst exhibited surface area of about 86 m2g−1. X-ray diffractionmeasurements indicated the formation of NiO and La2O3phases whilst NiO and spinel NiLa2O4formswere reduced to metallic Ni during H2reduction. Catalytic activity seemed to be stable with time-on-stream beyond 5–7 h and both C2H5OH and CO2conversions reached to 45.5% and 36.3%, respectively withvarying CO2partial pressure from 0 to 50 kPa. Significantly, H2/CO ratio varied from 1.3–2.3 favoured forFischer-Tropsch synthesis. The optimal C2H5OH partial pressure for reactant conversions was observedat 30–40 kPa. Reaction temperature varied from 923 to 973 K enhanced C2H5OH conversion about 167%.The heterogeneous nature of carbonaceous deposits including filamentous and graphitic carbons on thesurface of spent catalyst was evidenced by SEM, TEM and Raman analyses. However, carbon nanofilamentappeared to be predominant with concentration of 69.8%.